Shear bearing capacity calculation of low-rise SFRC shear wall with CFST columns based on simplified softened strut and tie model - You, Peibo; Li, Li; Qin, Yapeng; Wang, Yi; Yang, Qingjie; Zhang, Jie (Frontiers in Materials, 2024)
In the paper, an innovative shear wall, which is referred to as steel fiber reinforced concrete (SFRC) shear wall with concrete filled steel tube (CFST) columns, is introduced, based on the high bearing capacity and large stiffness of concrete filled steel tube column (CFSTC) and good cracking resistance and strong toughness of steel fiber reinforced concrete. The loading mechanism of steel fiber reinforced concrete shear wall (SFRCSW) with concrete filled steel tube columns is analyzed, and shear bearing capacity calculation method. A simplified model of the steel fiber reinforced concrete shear wall web softening tension bar is proposed, concrete and distributed web reinforcement to the shear bearing capacity of steel fiber reinforced concrete shear wall web is identified. Furthermore, a new algorithm to obtain the shear bearing capacity of steel fiber reinforced concrete shear wall with concrete filled steel tube columns is established, and then it is validated by using the test results of steel fiber reinforced concrete shear wall with concrete filled steel tube columns under low-cycle repeated loading. The results showed that all tested shear wall specimens exhibited obvious shear failure characteristics and a typical diagonal cracking pattern after test. The steel fibers obviously improved the crack forms of the steel fiber reinforced concrete shear wall web and the seismic behavior of steel fiber reinforced concrete shear wall with concrete filled steel tube columns.In addition, the proposed calculation method is scientific and accurate to analyze and predict the shear bearing capacity of low-rise steel fiber reinforced concrete shear wall with concrete filled steel tube columns.